Role of current, voltage and spark on-time on electrode material migration during EDM - Khan, Ahsan Ali; Mohd Noh, Nurul Shima (International Islamic University Malaysia, 2011)
Abstract. In the present work the influence of current, voltage and spark on-time on electrode material migration to the workpiece has been investigated. It was found that when the current or voltage is high, a spark with higher energy is produced and mote electrode material is melted and migrated to the work surface. When spark on-time is higher, more time is available for the copper electrode to be melted and migrated to the workpiece.